ANALISIS TEKNIKAL SAHAM MENGGUNAKAN INDIKATOR BOLLINGER BANDS DAN RELATIVE STRENGTH INDEX UNTUK PENGAMBILAN KEPUTUSAN INVESTASI - Gidion Willy Roy (Jurnal Manajemen, 2016)
The purpose of this study was to determine the condition of buying and selling shares in technical analysis. The object of this research is the price of BBCA and BBTN during 2015. Data were analyzed using Bollinger Bands and RSI. The findings in this study are buying conditions occur when the stock touches or is outside the lower band and at the same time RSI in oversold. While selling conditions occur when the stock touches or is outside the upper band and the same time also the RSI at overbought. Keywords: Technical Analysis, Bollinger Bands, RSI